Freedom's debtors : British antislavery in Sierra Leone in the age of revolution - Scanlan, Padraic X. ([Place of publication not identified] : Yale University Press : Yale University Press, 2017)
A history of the abolition of the British slave trade in Sierra Leone and how the British used its success to justify colonialism in Africa.
Cover; Half Title; Title; Copyright; Dedication; Contents; Acknowledgments; Introduction; 1. Antislavery on a Slave Coast; 2. Let That Heart Be English; 3. The Vice- Admiralty Court; 4. The Absolute Disposal of the Crown; 5. The Liberated African Department; Epilogue: MacCarthy's Skull; Notes; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Antislavery movements -- Sierra Leone -- History; Slavery -- Sierra Leone -- History; Mouvements antiesclavagistes -- Sierra Leone -- Histoire; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Antislavery movements; Slavery; Sierra Leone; History